2020
DOI: 10.1186/s13104-020-04987-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of pluripotent pig embryonic stem cells originating from uni- and biparental embryos

Abstract: Objectives: Pig pluripotent stem cells have tremendous potential because the pig is a valuable animal as both an agricultural resource and as a preclinical model of human therapy. To date, a lack of understanding of pig pluripotency has inhibited the derivation of embryonic stem cells (ESCs) and transgene-free induced pluripotent stem cells. Therefore, there has been no accessible or reliable transcriptome data for researching the genuine pig pluripotency network. Our previous study isolated authentic pig ESCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In the reproductive area, the generation of PGCLCs in vitro would assist in understanding the mechanisms involved in cellular differentiation and the epigenetic changes. PGCLCs, formed from nonembryonic sources, would be a suitable alternative for studies which are difficult to perform in humans 13,18–20 . In addition, due to the advantages of easy obtainment and abundant material sources, the differentiation of SDSCS into GCs has received extensive attention 17,21–23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reproductive area, the generation of PGCLCs in vitro would assist in understanding the mechanisms involved in cellular differentiation and the epigenetic changes. PGCLCs, formed from nonembryonic sources, would be a suitable alternative for studies which are difficult to perform in humans 13,18–20 . In addition, due to the advantages of easy obtainment and abundant material sources, the differentiation of SDSCS into GCs has received extensive attention 17,21–23 .…”
Section: Introductionmentioning
confidence: 99%
“…PGCLCs, formed from nonembryonic sources, would be a suitable alternative for studies which are difficult to perform in humans. 13,[18][19][20] In addition, due to the advantages of easy obtainment and abundant material sources, the differentiation of SDSCS into GCs has received extensive attention. 17,[21][22][23] As early as 2006, Dyce et al 24 demonstrated that SDSCs isolated from porcine fetal skin can be induced to PGCLCs in vitro, but the efficiency was very low.…”
Section: Introductionmentioning
confidence: 99%
“…This medium not only allowed for the expansion of SOX2-expressing cells from the ICM outgrowths, but also enabled the derivation of stable pESC lines from both IVF- and parthenogenetically-derived embryos ( Choi et al, 2019 ). pESC lines were stably maintained for more than 1 year while maintaining stemness and a normal karyotype ( Choi, Lee, Oh, Kim, Lee, Woo, et al, 2020 ). Interestingly, RNA-seq analysis showed that pESCs are transcriptionally closer to an epiblast-like state than to the ICM state ( Secher et al, 2017 ; Choi, Lee, Oh, Kim, Lee, Kim, et al, 2020 ).…”
Section: Recent Progress In Ppscs Derived From Porcine Embryosmentioning
confidence: 99%
“…pESC lines were stably maintained for more than 1 year while maintaining stemness and a normal karyotype ( Choi, Lee, Oh, Kim, Lee, Woo, et al, 2020 ). Interestingly, RNA-seq analysis showed that pESCs are transcriptionally closer to an epiblast-like state than to the ICM state ( Secher et al, 2017 ; Choi, Lee, Oh, Kim, Lee, Kim, et al, 2020 ).…”
Section: Recent Progress In Ppscs Derived From Porcine Embryosmentioning
confidence: 99%
“…The Wannan Chickens is a local breed of chicken native to China, with a distribution that extends along the river in southern and eastern Anhui. In recent years, transcriptome analysis has been employed extensively applied to study of various species and traits ( Choi, et al, 2020 ; Cassar-Malek, et al, 2022 ; Jin, et al, 2022 ), Furthermore, it has been successfully employed in the study of poultry traits ( Ren, et al, 2021 ; Pham, et al, 2022 ; Sun, et al, 2023 ). Weighted gene co-expression network analysis ( WGCNA ) has also been widely used to identify key modules of traits and important genes in a multitude of species ( Fan, et al, 2023 ; Yu, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%